PEMERIKSAAN MIKROSKOPIS KUALITAS SEDIAAN TELUR CACING Trichuris trichiura MENGGUNAKAN METODE NATIF DAN METODE FLOTASI - Nurhidayanti; Indah Sari (IKesT Muhammadiyah Palembang, 2023)
Background: Cases of helminthiasis in children are more often infected by Soil Transmitted Helmint (STH) worms, one of which is Trichuris trichiura (whipworm). Stool examination aims to determine the presence or absence of worm eggs or infective larvae. Examination of worm eggs by native and flotation methods is a qualitative examination, each of which has advantages and disadvantages. In the native method, the process is fast, but less sensitive in mild infections. The flotation method has the advantage that the field of view of the microscope is free from faeces so that it is easier to read on a microscope. The drawbacks of the flotation examination are that it takes quite a long time and is more suitable for use in feces that contain small amounts of worm eggs. Purpose: to see the quality of Trichuris trichiura worm egg preparations native and flotation methods. Research Methods: This method is used as an alternative because the native method still has drawbacks, especially in mild infections. This type of research is descriptive analysis. The research was conducted in the Hematology Laboratory of the Muhammadiyah Palembang Institute of Health Sciences and Technology on January 3, 2022 with a total sample of 32 preparations. Results: the study found that the flotation method was more optimal in detecting Trichuris trichiura worm eggs than the native method, with very good quality assessment results on the flotation method 10 preparations of 16 preparations (62.5%), while the native method obtained very good results for 3 preparations of 16 preparations (18.8%). Conclusion: from the research results, there are differences in the results between the flotation method and the native method.